2015
DOI: 10.1007/s12298-015-0309-z
|View full text |Cite
|
Sign up to set email alerts
|

Capsule formation and asymbiotic seed germination in some hybrids of Phalaenopsis, influenced by pollination season and capsule maturity

Abstract: We explored the influence of pollination season and maturity of capsule on post-pollination capsule formation and in vitro asymbiotic seed germination, respectively. Three Phalaenopsis orchid hybrids, namely, 'Athens', 'Moscow' and 'Lusaka' flowers were artificially self-pollinated during winter, spring, summer and fall seasons and the impact of the pollination seasons was evident during capsule formation. It was observed that winter was the most suitable season for pollination of all the three Phalanaeopsis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…requires 7–9 months to mature (Ávila‐Díaz et al, 2009 ). As noted here and in other studies, the age of seeds can have a strong effect on germination (Tsuchiya, 1954 ; Balilashaki et al, 2015 ; Zhang et al, 2015 ; Kendon et al, 2017 ). Seeds harvested too early may germinate but then fail to develop further, whereas seeds harvested when fully mature can have reduced germination rates.…”
Section: Discussionsupporting
confidence: 80%
“…requires 7–9 months to mature (Ávila‐Díaz et al, 2009 ). As noted here and in other studies, the age of seeds can have a strong effect on germination (Tsuchiya, 1954 ; Balilashaki et al, 2015 ; Zhang et al, 2015 ; Kendon et al, 2017 ). Seeds harvested too early may germinate but then fail to develop further, whereas seeds harvested when fully mature can have reduced germination rates.…”
Section: Discussionsupporting
confidence: 80%
“…Lots of propagation techniques were developed for Phalaenopsis species and their hybrids through the in vitro culture from various explants, including leaf segments/tissue [3], flower stalk nodes [4], callus and protocorm-like bodies [5], flower stalks [6], and seeds [7, 8]. However, propagation through in vitro seed culture has not yet been achieved in P. amboinensis orchid.…”
Section: Introductionmentioning
confidence: 99%
“…According to McCall and Primack (1992) environmental circumstances considerably affect the fruit/seed development that was noticeably manifested from the outcomes of the current experiment. Further, the advantageous impact of cooler seasons on efficacious post-pollination capsule development coroborated by the studies of Vaknin et al (1996) and Balilashaki et al (2015), who reported that the frequency of fruit set was lesser in summer in comparison to winter ones in Loranthus acaciae Zucc. (Loranthaceae) and Phalaenopsis respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Seeds were isolated by softly teasing the surface sterilized slitcapsules with scalpel and cultured on different media: the surface of half-strength Murashige and Skoog (1962) (MS), Vacin-Went (VW) (Vacin and Went, 1949) or modified (supplemented with pepton) Chen medium (Chen et al, 1999), solidified with 0.25% (w/v) Gelrite (Balilashaki et al, 2015). The media pH were corrected to 5.7 before autoclaving at 121 °C and 105 kg cm −2 for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation